ANALISIS FAKTOR PENYEBAB KECELAKAAN KERJA PADA BAGIAN FLEXO FINISHING DI PERUSAHAAN MANUFAKTUR - Faizah Nur Hasanah; Evi Widowati (Jurnal Kesehatan Masyarakat, 2022)
Batam is the city with the highest number of work accident cases in Riau Islands Province, which dominated by the industrial sector with an annual percentage of > 85%. Company X is the industry with the largest packaging box production in Batam . Based on the company's work accident report in 2016 there were 12 cases, in 2017 there were 9 cases, in 2018 there were 12 cases, in 2019 there were 20 cases and in 2020 there were 12 cases. The highest work accident cases are in the flexo finishing production section. This study aims to determine the factors that cause work accidents in the flexo finishing section in manufacturing company. The type of this research is analytic observational with quantitative approach and cross sectional study design. The research sample of 50 samples was taken using a total sampling technique. The instrument used is a questionnaire. Data analysis using chi-square test. The results showed that there was a relationship between OHS training (p=0.022) and the use of PPE (p=0.003) with work accident. There is no relationship between age (p=0.087) and work period (p=0.383) with work accident. The suggestion of this research is that there is a need for a re-evaluation in the implementation of the OHS training program and the use of PPE, by providing OHS training equally to all workers and providing PPE in accordance with the potential hazards and risks of work accidents in the work section.